Genomic characteristics of monkeypox virus from 8 cases in Changning District， Shanghai - HE Xiaoding; XU Yang; YIN Ning; WANG Zhenyu; GUO Jiayin (Shanghai yufang yixue)
ObjectiveTo investigate the epidemiological feature of Mpox infection and genetic characteristics of Mpox viruses (MPXVs), so as to understand the etiological evolution of the pathogen.MethodsThe cases infected with MPXVs were originated from Changning District, Shanghai from July 20 to August 24 in 2023. Epidemiological investigations were conducted, and throat swabs, anal swabs, or vesicle fluid were collected for MPXVs nucleic acid testing. High-throughput sequencing was performed using Miniseq of the Illumina sequencing platform, and thereafter the sequences were concatenated and analyzed using the online analysis tool Nextclade. An evolutionary tree was constructed using the MEGA 11 software.ResultsAll 8 cases were male, with an average age of (35.76±7.00) years. Among them, 6 cases were identified through active hospital visits, and 2 cases were discovered during contact tracing for Mpox cases. Within the 21 days preceding the disease onset, all cases had male-male sexual behaviors, and the incubation period ranged from 6 to 10 days. 3 cases had a history of sexually transmitted diseases (STDs). MPXVs nucleic acid testing indicated that the detection rate of MPXVs was found to be 25.00% for throat swabs, 87.50% for anal swabs, and 100.00% for vesicle fluid, with statistically significant differences (χ2=11.052, P=0.004). Sequencing analyses using the online tool Nextclade indicated that all 8 MPXVs belonged to the West African clade Ⅱb, 4 MPXVs were classified as C.1 sub-lineages, and 4 MPXVs were identified as C.1.1 sub-lineages. Phylogenetic analysis using MEGA 11 indicated that 5 MPXVs were classified as Lineage C.1.1, closely related to the prevalent strains in Portugal and other European regions.ConclusionThe MPXVs sequences from Changning District are clssified into clade Ⅱb, lineage C.1.1. The detection rates of vesicle fluid and anal swabs for MPXVs are significantly higher than that of throat swabs.